2023
DOI: 10.3389/feduc.2023.1191817
|View full text |Cite
|
Sign up to set email alerts
|

Students’ digital addiction and learning difficulties: shortcomings of surveys in inclusion

Abstract: Students have been distance learning to a considerable extent during the Covid years and the primary concerns are teenagers’ learning difficulties, digital addiction and long screen time. Our aim was thus to study teenagers’ perceived learning difficulties, digital addiction and screen time. The current study was a part of a larger e-survey. The data were collected across Estonia from 8,486 teenagers who studied in the inclusive education system during spring 2022. The students were 11–20 years old. While anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similarly, Seema and colleagues (2022) found that the presence of symptoms of digital addiction was associated with poorer engagement in learning, higher levels of burnout due to learning, and the presence of learning disabilities (Seema et al, 2022;Seema & Varik-Maasik 2023). One of the reasons may be the habitual use of frequent digital devices, which diverts attention away from learning (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Seema and colleagues (2022) found that the presence of symptoms of digital addiction was associated with poorer engagement in learning, higher levels of burnout due to learning, and the presence of learning disabilities (Seema et al, 2022;Seema & Varik-Maasik 2023). One of the reasons may be the habitual use of frequent digital devices, which diverts attention away from learning (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sadly, students with learning difficulties may find answering a questionnaire difficult, therefore there may be students with learning difficulties whose answers were left out of analysis. Students with learning difficulties may need some extra attention and help with filling in any long questionnaire (Seema & Varik-Maasik, 2023).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…College students need to learn proper time management strategies. More research needs to be conducted on this topic to better address the issue and improve the techniques in the future [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…While digital technologies offer benefits like skill development and resource accessibility (Costley, 2014), the rise of internet addiction among university students presents a significant concern (Mhlongo et al, 2023;Seema & Varik-Maasik, 2023). Fan et al (2023) highlight its negative impacts, including emotional abuse, neglect, and mental health issues.…”
Section: Introductionmentioning
confidence: 99%